2019
DOI: 10.3390/nu12010018
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Cultural Immersion on Willingness to Try Fruits and Vegetables among Children in Guam: The Traditions Pilot Study

Abstract: Culturally relevant programs among indigenous populations have had positive dietary outcomes, yet less is known about cultural immersion. This study examined the influence of cultural immersion on willingness to try fruits and vegetables (FV) among children 3‐12 y in Guam. A pre‐post, quasi‐experimental design was used to evaluate 3 summer camps with different exposure levels of cultural immersion. High, moderate, and zero exposure was provided by a cultural immersion camp (CIC), a university‐based day camp (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The consumption of traditional F&Vs (and likely other traditional foods) in American Samoa, despite westernization, also demonstrates the preservation and perpetuation of traditional practices as a leverage point to adopting a healthy diet in the Pacific. For high-income Pacific economies, such as CNMI, Guam, and Hawaii, placing more value on and increasing traditional ways of living may assist in promoting the regulation of imported foods and support increased consumption of locally grown produce to advance the nutrition transition to desired societal/behavioral change ( 1 , 4 , 13 , 19 ). These observations would support policies for cultural preservation, a self-sustaining local food system, and regulation of imports to achieve optimal food security.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of traditional F&Vs (and likely other traditional foods) in American Samoa, despite westernization, also demonstrates the preservation and perpetuation of traditional practices as a leverage point to adopting a healthy diet in the Pacific. For high-income Pacific economies, such as CNMI, Guam, and Hawaii, placing more value on and increasing traditional ways of living may assist in promoting the regulation of imported foods and support increased consumption of locally grown produce to advance the nutrition transition to desired societal/behavioral change ( 1 , 4 , 13 , 19 ). These observations would support policies for cultural preservation, a self-sustaining local food system, and regulation of imports to achieve optimal food security.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional food systems of the Ka Tu are undermined by the government. However, studies have shown that there is a sense of pride and identity among indigenous peoples' traditional food systems which can protect the health of a community [66,67]. Programmes could engage agricultural and community actors to create communal vegetable gardens for patients or create cooking workshops with locally sourced products to overcome this.…”
Section: Discussion: Lessons For Decentralised Ncd Programmesmentioning
confidence: 99%
“…Children’s willingness to try new foods and FV were assessed using the validated Adapted WillTry tool for children 3–11 years in Guam [ 13 , 19 , 20 ]. Only FV data will be reported in this study, which were captured in one of four FV scales in the Adapted WillTry tool: local novel (6 items), local common (4 items), imported (3 items), and total FV (14 items) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Trained research staff conducted one-to-one interviews with children, where children self-reported their willingness to try new foods and FV. These methods have been tested in a similar population in Guam and described elsewhere [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation